스위트 다크 체리의 영양성분 및 항산화 활성 - 구권순; 김일훈; 정창호; 금동찬; 장치원; 김영숙; 이구열; 심기환; Gwon-Sun Gu; Il-Hun Kim; Chang-Ho Jeong; Dong-Chan Kum; et al. (농업생명과학연구, 2014)
스위트 다크 체리를 기능성 식품 소재로 이용하기 위한 기초자료를 제공하기 위하여 화학성분 및 항산화 활성을 조사하였다. 체리 착즙액의 pH는 4.06, 가용성고형분은 29.30 °Brix 및 총산도는 0.60%였으며, L, a, b값은 각각 21.56, 3.99 및 1.12였다. 일반성분 함량은 수분 67.74%, 조단백 0.98%, 조지방 1.46%, 가용성 무질소물 28.40%, 조섬유 0.45% 및 조회분 0.89%였다. 주요 무기성분은 칼륨, 인 및 칼슘으로 그 함량은 각각 216.86 mg/100 g, 56.97 mg/100 g 및 32.97 mg/100 g이었다. 주요 유리당으로는 glucose(4.91%)와 fructose(3.88%)이며, 아미노산으로는 aspartic acid, proline, glutamic acid 및 leucine이었고, cystine과 methionine은 매우 낮은 함량을 보였다. 비타민 C와 총 페놀성 화합물 함량은 0.81 mg/100 g과 0.31 mg/GAE g였으며, 라디칼 소거활성, 환원력 및 지질과산화 억제활성은 농도의존적인 경향을 보여 체리는 기능성 식품 소재로 활용가능성이 높을 것으로 판단된다. In this study, the nutrition components and antioxidative activities of sweet dark cherry fruit were investigated. The values of pH, soluble solids, and total acidity were 4.06, 29.3 Brix and 0.60% respectively. Hunter L, a, and b values were 21.56, 3.99 and 1.12, respectively. Proximate compositions were as follows: moisture 67.74%, crude protein 0.98%, crude fat 1.46%, nitrogen free extract 28.48%, crude fiber 0.45% and ash 0.89%. Mineral components of cherry was rich in K (216.86 mg/100 g), P (56.97 mg/100 g) and Ca (32.97 mg/100 g). The major free sugars of cherry were glucose(4.91%) and fructose(3.88%). An analysis of the component amino acid showed a relatively high ratio of aspartic acid, proline, glutamic acid and essential amino acids of leucine, but a low cystine and methionine content. Contents of ascorbic acid and total phenolics were 0.81 mg/100 g and 0.31 mg/GAE g, respectively. The radical scavenging activities, reducing power and inhibitory effect of lipid peroxidation were dose-dependent. Thus, cherry can be an effective source of functional food substances.